Experiencing Intimate Partner Violence (IPV) Is Associated with Psychosocial Health Problems Among Gay, Bisexual, and Other Men Who Have Sex with Men (GBMSM) in Nigeria, Africa - Ogunbajo, Adedotun (Journal of interpersonal violence, 2022)
Previous research has shown high rates of intimate partner violence (IPV) among gay, bisexual, and other men who have sex with men (GBMSM). Experiencing IPV may predispose GBMSM to psychosocial health problems. A vast majority of the research on IPV among GBMSM have been conducted in North America and Europe. To date, no published studies that we are aware of have investigated the prevalence and correlates of IPV among GBMSM in West Africa. To fill this gap in research, the present study investigated the prevalence of IPV and its? association with psychosocial health problems in a large multicity sample of community-recruited GBMSM in Nigeria. Bivariate and multivariable logistic regression analyses were utilized to examine associations between sociodemographic characteristics, psychosocial health problems, sexual risk, and experiences of IPV (N = 389). The prevalence of experiencing emotional, physical, sexual, monitoring behaviors, and controlling behavior were 45%, 31%, 20%, 55%, and 22% respectively. Experiencing all types of IPV, except physical violence, was significantly associated with increased odds of having depressive symptoms (Adjusted OR [AOR] 1.79?2.63; 95% confidence interval [CI]: 1.08?4.60) and anxiety (AOR 1.63?2.63; 95% CI: 1.01?4.18). Experiencing emotional violence (standardized beta [?] = 0.21; standard error [SE] SE = 0.44), physical violence (? = 0.14; SE = 0.48), and controlling behaviors (? = 0.11; SE = 0.54) was associated with increased odds of loneliness. Experiencing all types of IPV was associated with history of suicide thoughts (AOR 2.20?3.68; 95% CI: 1.28?6.32) and suicide attempt (AOR 2.36?3.42; 95% CI: 1.20?6.75). Additionally, we observed a dose?response relationship, whereby increasing number of IPV was associated with a higher likelihood of reporting psychosocial health problems. Lastly, after adjusting for other psychosocial health problems and demographic characteristics, there remained a significant association between experiencing IPV and reporting a history of suicide thoughts and suicide attempt. Consequently, it is imperative that health interventions aimed at improving psychosocial health of GBMSM explore experience and perpetration of IPV.